STUDY ON AGE RELATED MACULAR DEGENERATION (DRY TYPE) IN CONTEXT TO PITTA VIDAGDHA DRISHTI AND ITS AYURVEDIC MANAGEMENT - Kumar Soni, Rajendra; Srivastava, Garima; Dhiman, K. S.; Manjusha, R; Mehta, Amit J. (International Journal of Ayurveda and Pharma Research, 2015)
Age Related Macular Degeneration (ARMD) is the leading cause of the vision loss and blindness in people above 50 years of age. ARMD is characterised by central vision loss, distorted or blurred vision, decreased visual acuity, Central or para-central blind spot (scotoma). An almost similar clinical condition to ARMD is seen in Pitta Vidagdha Dristi. Dry ARMD is more prevalent (90%) and slower in progress than Wet ARMD. The Ayurvedic management of Pitta Vidagdha Drishti is similar to Pittaja Abhishyanda. With this background a specific line of treatment for the Pitta Vidagdha Drisht in Sushruta Samhita is adopted. In this study, total 22 patients, 12 in group A (Triphala Ghrita, Saptamrita Lauha, Rasayana Churna and Shatavari etc.) & 10 in Group B (Control) were registered. The duration of therapy was of 3 months in both the groups. Group A showed better results on ARMD when compared with that of Group B especially on perception of flashes of light (72.23%) & dim light adaptation problem (45.23%). So ARMD (Dry type) can be better managed by Ayurvedic treatment group than the Modern multivitamin group.